An Exploratory Study Interrelating Emotion, Self-Efficacy and Multiple Intelligence of Prospective Science Teachers - Hernández-Barco, Míriam; Cañada-Cañada, Florentina; Corbacho-Cuello, Isaac; Sánchez-Martín, Jesús (Frontiers in Education, 2021)
This research offers a descriptive and inferential analysis of the emotions toward the teaching of science felt by 144 second-year students of a Primary Education bachelor’s degree course, identifying their learning styles in accordance with the theory of Multiple Intelligences, studying their perception of self-efficacy concerning the different scientific contents they would need to teach, and establishing correlations between these variables. The investigation is quantitative in character, carried out via a survey, using SPSS and JASP for the data analysis. The results show that these prospective teachers feel greater rejection toward Physics and Chemistry than toward Biology and Geology (they mainly express enthusiasm for the latter). It is possible to establish differences in the emotions that the prospective teachers feel toward science depending on which path they took in their pre-university studies (Arts or Sciences). There are correlations between feeling positive emotions and having greater self-efficacy in teaching those same scientific topics. Those who feel negative emotions, such as fear or rejection, toward Physics and Chemistry have lower self-efficacy. There are correlations between having greater self-efficacy when teaching science and having a predominantly logical-mathematical intelligence. There is also a relationship between having a predominantly logical-mathematical type of intelligence and feeling more positive emotions toward sciences. Predictors of emotional dimension and self-efficacy have been also explored by multiple regression.